Mental Illness During Pregnancy: Schizophrenic Couples' Perspectives on Pregnancy - Tasijawa, Fandro Armando; Herwawan, Joan Herly; Madiuw, Devita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Schizophrenic patients during pregnancy have significant consequences such as gestational diabetes (especially when taking antipsychotics), gestational hypertension, venous thromboembolism, fetal growth restriction, stillbirth, premature delivery, and fetal anomalies. The quality of life of schizophrenic patients during pregnancy will never be realized without the support of all parties, including their partners. This study aims to explore the schizophrenic couple's perspective on pregnancy. The method used in this research is qualitative research using a descriptive phenomenological approach. Data collection techniques used 30-45 minutes of in-depth interviews and were analyzed using Colaizzi's seven stages. The results of this study found three themes, namely (1) sincerity in caring for those in distress, (2) Belief in God's destiny, and (3) Fear of having a child with a mental disorder. New insights in this research about 'sincerity in caring for in distress' can provide inspiration that there is still sincerity in caring for a sick partner in a difficult life. This research encourages health workers, especially nurses, to provide holistic and comprehensive health services to their partners.